Turning Digital Transformation to Sustainable Competitive Advantage: A Qualitative Multi-Case Study Across Industries - Elkana Timotius (Maneggio, 2026)
Digital transformation has become one of the most pressing strategic agendas for organizations seeking to maintain competitive advantage amidst rapid technological disruption. This article aims to analyze how the digital transformation process contributes to the formation of sustainable competitive advantage (SCA), by positioning dynamic capabilities and organizational agility as key connecting mechanisms. This research uses a qualitative multi-case case study approach based on document analysis and cross-case synthesis of several organizations across sectors—banking, tourism and hospitality, manufacturing, and small and medium enterprises—that have been published in the current literature. Data are analyzed thematically through stages of within-case and cross-case analysis to identify patterns, similarities, and contextual specificities. The results show that digital transformation does not automatically generate sustainable competitive advantage, but rather depends on the organization's capacity to build dynamic capabilities, strategic agility, and a culture of innovation that aligns with each organization's resource and institutional context. The novelty of this research lies in the integration of the Resource-Based View and Dynamic Capabilities Theory frameworks in a cross-sector and cross-country synthesis that has rarely been done in qualitative-comparative ways. Practical implications for managers and policy makers, limitations of the study, and directions for further research are also discussed at the end of the article.